Comparison of clinical characteristics and healthcare resource use of pediatric chronic and non-chronic critically ill patients in intensive care units: a retrospective national registry study - Grandjean, Chantal; Perez, Marie-Hélène; Ramelet, Anne-Sylvie; , The OCToPuS Consortium; Lauria, Anne-Laure; Polito, Angelo; Bochaton, Nathalie; Trachsel, Daniel; Marston, Mark; Schnidrig, Silvia; Humpl, Tilman; Rogdo, Bjarte; et al. (Frontiers in Pediatrics, 2023)
Introduction Chronic critically ill patients (CCI) in pediatric intensive care unit (PICU) are at risk of negative health outcomes, and account for a considerable amount of ICU resources. This study aimed to (a) describe the prevalence of CCI children, (b) compare their clinical characteristics and ICU resources use with non-CCI children, and (c) identify associated risk factors of CCI. Methods A retrospective national registry study including 2015–2017 data from the eight Swiss PICUs of five tertiary and three regional hospitals, admitting a broad case-mix of medical and surgical patients, including pre- and full-term infants. CCI patients were identified using an adapted definition: PICU length of stay (LOS) ≥8 days and dependence on ≥1 PICU technology. Results Out of the 12,375 PICU admissions, 982 (8%) were CCI children and compared to non-CCI children, they were younger (2.8 vs. 6.7 months), had more cardiac conditions (24% vs. 12%), and higher mortality rate (7% vs. 2%) (p < 0.001). Nursing workload was higher in the CCI compared to the non-CCI group (22 [17–27]; 21 [16–26] respectively p < 0.001). Factors associated with CCI were cardiac (aOR = 2.241) and neurological diagnosis (aOR = 2.062), surgery (aORs between 1.662 and 2.391), ventilation support (aOR = 2.278), high mortality risk (aOR = 1.074) and agitation (aOR = 1.867). Conclusion the results confirm the clinical vulnerability and the complexity of care of CCI children as they were defined in our study. Early identification and adequate staffing is required to provide appropriate and good quality care.